Techno-nationalism and techno-globalism conflict and cooperation - Ostry, Sylvia A.; Nelson, Richard R. 1930- (Brookings Inst., 1995)
Because governments increasingly believe that long-term wealth creation depends on superior technical skills, they are inclined to provide direct or indirect assistance to potential technological winners. This raises the risk of trade and subsidy wars
Keywords: Geschichte 1900-2000; Concurrentie; ECONOMIC ASPECTS; ECONOMIC HISTORY; Hoogwaardige technologie; JAPAN; TECHNOLOGICAL INNOVATIONS; Technische vernieuwing; UNITED STATES; Geschichte; Industrie; Wirtschaft. Geschichte; Competition, International -- History -- 20th century; Economic history -- 1945-; Industries -- Japan -- History -- 20th century; Industries -- United States -- History -- 20th century; Technological innovations -- Economic aspects -- Japan -- History -- 20th century; Technological innovations -- Economic aspects -- United States -- History -- 20th century; Wirtschaftsentwicklung; Spitzentechnologie; USA; Japan